2017
DOI: 10.1186/s12879-017-2725-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure rate of VZV among women attending antenatal care clinic in Sri Lanka - a cross sectional study

Abstract: BackgroundVaricella or chickenpox was not a notifiable disease until 2005 in Sri Lanka and only a few studies have been conducted on the epidemiology of VZV infection in the country. The anti­VZV IgG sero-prevalence among antenatal women is extremely limited and thus a selected group of antenatal clinic attendees were chosen to determine the exposure rate to VZV infection.MethodsWomen attending the antenatal clinic at Teaching Hospital, Peradeniya, Sri Lanka were selected for the study and 3 mL of venous blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…There is also a possibility of waning antibody titres following infections during early life. These findings are comparable to the results of other Sri Lankan [15] and international studies [21, 25].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There is also a possibility of waning antibody titres following infections during early life. These findings are comparable to the results of other Sri Lankan [15] and international studies [21, 25].…”
Section: Discussionsupporting
confidence: 91%
“…This is comparable to the 62% rate detected in the study done among women of childbearing age in Colombo district [14]. However, the study conducted among pregnant women in Peradeniya, Sri Lanka detected a slightly higher seroprevalence of 77.9% [15]. This could be due to differences in climatic factors of the two areas, where Peradeniya is situated in the central province of the country, in a cooler climatic zone and Colombo is situated in the western province in a warmer area.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, in the recent past, one of our studies reported an increased exposure rate of 78% to VZV in a group of antenatal women aged between 18 and 45 years. Moreover, in the study sample, those that were more than 40 years had a sero-prevalence of 100% to anti-VZV IgG and thus an increment in the exposure rate to VZV was noted with increasing age [14].In a more recent study conducted in Sri Lanka, the overall anti-VZV IgG sero-prevalence in the women of childbearing age was 62% and it was as low as 37% in the 15-19 years age group [35].…”
Section: Prevalence Of Vzv Infection In Sub-tropical and Tropical CLImentioning
confidence: 72%